Green Synthesis and Characterization of Cu and Cu2O Nanoparticles and its Biological Activities Using Urginea indica: Pharmaceutical Science-Nanotechnology - Raveesha, H R; L, Esther Pramila (International Journal of Life Science and Pharma Research, 2022)
In the past decade, the development of metal nanoparticles in an eco-friendly manner has become an important aspect in the field of nanotechnology. Our present study reports the utilization of Urginea indica (U. indica) bulbs for the synthesis of copper (Cu) and copper oxide nanoparticles (Cu2O NPs). Cytotoxic activity against colon (HCT-116) carcinoma cell lines as well as their antibacterial and scavenging potential were determined. The green synthesized copper nanoparticles were confirmed using various analytical characterization techniques. The cytotoxic effect of the NPs was studied by MTT assay, and scavenging efficacy was assessed by DPPH and ABTS assays. Furthermore, green synthesized nanoparticles were evaluated for their antibacterial activity by the Agar disc diffusion method against multidrug-resistant bacterial strains. The nanoparticles were observed to be almost spherical in shape with an average diameter of 66.99nm as assessed by SEM analysis. Nanoparticles revealed dose-dependent antioxidant activity and antimicrobial activity against bacterial strains viz. Enterococcus faecalis, Bacillus cereus, Escherichia coli, Serratia marcescens, and also in vitro studies revealed dose-dependent cytotoxic effects treated against HCT-116 cell line with IC50 of 56.726 μg/mL. The data obtained in the study shows that Cu-Cu2O NPs obtained from U. indica bulbs have potent therapeutic value in the pharmaceutical industry.